Reinforcement of the Framework for Experiential Education in Healthcare in Serbia: Post-Implementation Project Review within Pharmacy Education - Marina Odalović; Jelena Parojčić; Dragana Vasiljević; Danijela Đukić Ćosić; Ljiljana Tasić (MDPI AG, 2019)
Background: The Erasmus+ project “Reinforcement of the Framework for Experiential Education in Healthcare in Serbia” (ReFEEHS) has been undertaken with the aim to: (i) reinforce and modernize experiential education (ExEd) in the health sciences curricula, (ii) introduce interprofessional education (IPE), and (iii) promote teaching competency development of academic staff and teacher practitioners/clinician educators. The aim of this paper is a post-implementation review of the project activities and outcomes with the emphasis on the impact and sustainability in pharmacy education. Methods: Project Logical framework matrix has been employed as planning, monitoring and evaluation tool which summarizes the main project objectives, project outcomes, relevant activities, indicators of progress, sources of verification, assumptions and risks. Results: The key project outcomes are: (i) update of competency-based curricula and development of quality assurance framework for students professional practice placements; (ii) development and introduction of interprofessional teaching and learning activities through joint curriculum delivery; and (iii) development and implementation of Teaching Certificate in Health Professions Education (TCinHPE) study program. The short-term impact of project activities and outcomes has been assessed based on the feedback received from relevant stakeholders, as well as self-evaluation of participants enrolled in new/updated curricula. Sustainability of project results is necessary in order to achieve long-term impact envisioned as increased level of professional competency of health science students; increased level of teaching competency of academic staff and teacher practitioners; improved patient healthcare and harmonisation with the EU practice and policies. Conclusions: The project outcomes contributed to building capacity at the Serbian universities involved in terms of collaboration between the healthcare professions and, in curriculum and academic staff development. It is expected that improved curricula will positively impact professional competency development of pharmacy students, graduates employability and increased workforce mobility. Meeting the quality standards of the European Higher Education Area will contribute to visibility of Serbian universities and their internationalisation, which is one of the strategic aims of improvement.